ABUNDANCE AND SPECIES RICHNESS OF MACROZOOBENTHOS AND THEIR RELATIONSHIP TO TEXTURE AND ORGANIC MATTER IN SEDIMENTS IN THE UPPER CITARUM WATERSHED - Fadiya, Dafa
The Citarum River plays an important role in supplying water to fulfill the people needs around river. However, this is not followed by protecting the river from pollution. The upstream area is an area that has the potential to receive high organic waste. Accumulation of organic matter in sediments is thought to cause a decrease in species richness and abundance of macrozoobenthos. This study aims to determine the level of organic pollution in sediments and its relationship with the presence of macrozoobenthic communities in the Upper Citarum River Basin. Sampling was conducted at 3 stations, namely Situ Cisanti, Sapan, and Dayeuhkolot in the period March - April 2023. The environmental factors measured were temperature, DO, pH, salinity, TDS, TSS, organic matter, and texture. Macrozoobenthos was collected from each station using Eckman Grab. Data analysis was performed with pearson correlation and PCA. The results showed that the levels of organic contamination in sediments from the highest to the lowest were Sapan, Dayeuhkolot, and Situ Cisanti. Sapan has a value of organic matter in sediments ranging from 16.93% to 20.52% which is included in the medium to high criteria, characterized by a silty clay to silt texture and there are 3 species with 0 to 104 individuals/m2. Dayeuhkolot has a value of organic matter in sediments ranging from 15.11% to 17.45% which is included in the medium to high criteria, characterized by a silty clay texture, and there are 5 species with 193 to 1111 individuals/m2. While Situ Cisanti has a value of organic matter in sediment ranging from 9.76% to 11.81% which is included in the moderate criteria, characterized by sand texture, and there are 10 species with 133 to 163 individuals/m2. Differences in the amount of organic matter input and the type of texture for each station result different organic matter content and affect species richness and abundance. It is suspected that Sapan waters receive a lot of pesticide input from agricultural activities around the river which results in high rainfall so that surface runoff water directly enters the river. Based on its correlation, abundance and species richness decreased when organic matter in the sediment increased and the texture was dominated by silt and clay. This shows that contamination of organic matter in sediments can endanger macrozoobenthos life which has an impact on disruption of aquatic ecosystems because of the important role of macrozoobenthos in assisting the decomposition process and be part of various trophics in the food chain.